Relationship between Scientific Reasoning and Scientific-Mathematical Content Knowledge in International General Certificate of Secondary Education and International Baccalaureate Diploma Programs - Dinçer Akış; Akin Metli (Sakarya Üniversitesi Eğitim Fakültesi Dergisi)
Abstract. Scientific reasoning skills help students master scientific competencies, understand complex concepts, and equip them with the abilities to apply concepts and competencies in a variety of real-life contexts. These skills are important for students’ preparation to the international education programs. Since there are limited studies in the literature that examine the relationship between students’ content knowledge and scientific reasoning, especially in the international programs in secondary education, this research aims to investigate the extent to which the students’ achievement in the International General Certificate of Certificate (IGCSE) as well as students’ achievement in their science and mathematics courses in the International Baccalaureate Diploma Program (IBDP) correlate to the students’ scientific reasoning abilities. The research was conducted at a national school with IGCSE and IBDP programs. The study used Classroom Test of Scientific Reasoning (CTSR) to measure the scientific reasoning. The students’ performances in the CTSR and their levels of achievement in science and math in the IGCSE and IBDP were analyzed using Pearson’s correlation test and Kendall’s tau-b correlation test. The results revealed that there is a moderate correlation between scientific reasoning and content knowledge in science and mathematics.